PENGUATAN RESILIENSI UMKM MELALUI MANAJEMEN RISIKO BERBASIS ISO 31000: 2018 PADA ERA TRANSFORMASI DIGITAL: TINJAUAN LITERATUR SISTEMATIS - Puri Rohmatulloh; Ana Ima Sofana (Universitas La Tansa Mashiro, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the economies of developing countries through their contribution to employment generation and Gross Domestic Product (GDP). However, the acceleration of digital transformation has fundamentally reshaped the risk environment faced by MSMEs, leading to increasing complexity of operational, technological, and market-related risks amid persistent limitations in internal resources and managerial capabilities. This study aims to systematically review how ISO 31000:2018-based risk management practices contribute to strengthening MSMEs resilience in the digital transformation era. Employing a Systematic Literature Review with a qualitative descriptive approach, this study analyzes peer-reviewed journal articles and accredited scientific publications published between 2018 and 2025. Content analysis is used to examine the alignment of ISO 31000 principles, frameworks, and process stages with risk management practices in both traditional and digital-based MSMEs, as well as their implications for organizational resilience. The findings reveal that most MSMEs have not yet implemented comprehensive and integrated risk management, particularly in the stages of risk identification, analysis, evaluation, and treatment. Digital-based MSMEs tend to demonstrate higher levels of adaptability and resilience, supported by digital transformation, innovation capability, collaboration, and enabling government policies, whereas traditional MSMEs remain constrained by limited internal capacities and capabilities. This study highlights the urgent need to strengthen ISO 31000:2018-based risk management through enhanced risk literacy, capacity building, and context-sensitive implementation models to support the long-term resilience and sustainability of MSMEs in an increasingly digitalized business environment.